2019
DOI: 10.1007/jhep04(2019)126
|View full text |Cite
|
Sign up to set email alerts
|

Early scrambling and capped BTZ geometries

Abstract: Geodesic probes in certain horizonless microstate geometries experience extreme tidal forces long before reaching the region where these geometries differ significantly from the extremal BTZ black hole. The purpose of this paper is to show that this behavior is a universal feature of all geometries that have a long BTZ throat that terminates in a cap, regardless of the details of this cap. Hence, incoming probes will scramble into the microstate structure before they encounter the region where the charges of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(114 citation statements)
references
References 42 publications
6
108
0
Order By: Relevance
“…Both processes require some energy to be supplied. 24 One of the excitations that costs rather little energy is to pry a fundamental string loose from the background. In [67] it was shown that large gauge transformations in the SL(2, R) factor of G mediate processes by which F1 winding charge dissolved as background flux can be transferred to winding string excitations not bound to the cap.…”
Section: W-brane Excitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both processes require some energy to be supplied. 24 One of the excitations that costs rather little energy is to pry a fundamental string loose from the background. In [67] it was shown that large gauge transformations in the SL(2, R) factor of G mediate processes by which F1 winding charge dissolved as background flux can be transferred to winding string excitations not bound to the cap.…”
Section: W-brane Excitationsmentioning
confidence: 99%
“…The fully nonlinear field equations are solved, with the wave profile tuned to avoid singularities and other pathologies such as closed timelike curves. However, it has been shown [24,134] that probes of this geometry experience large tidal forces, an indicator that the large blueshift experienced by the probe will result in processes wellapproximated by the collision of gravitational shockwaves, resulting in a disruption of the delicately tuned superstratum structure. There will be plenty of excitation energy available to transfer angular momentum away from the supertube, causing it to evolve toward the regime where W-branes become light.…”
Section: The Role Of Microstate Geometriesmentioning
confidence: 99%
“…Nevertheless, quite a number of physically interesting microstate geometries are ultimately rather simple. Some can be reduced to (2+1)-dimensional backgrounds that are best described as smoothly capped BTZ geometries [2][3][4][5][6][7]. That is, the geometry is asymptotic, at infinity, to AdS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In some classes of these geometries, the massless scalar wave equation is even separable [4,[7][8][9]. This has enabled a great deal of analysis of such geometries and an investigation of their possible effects on microstructure [4,10,11,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation